Keterlibatan Aktor dalam Kerjasama Pengelolaan Corporate Social Responsibility (CSR) Badan Usaha Milik Daerah (BUMD) Provinsi Jawa Barat - Fauzi Akbar; Sam'un Jaja; Achmad Buchori; Sinta Ningrum (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
This study aims to determine the involvement of actors with a triple helix approach in cooperation in managing corporate social responsibility (CSR) of Regional-Owned Enterprises (BUMD) of West Java Province, given that CSR management during visits to West Java Province is expected to be able to support regional development budgets and one of the the door of the West Java Provincial government's sustenance from the eight priority doors of sustenance. This research method uses a qualitative method with a descriptive approach and uses data collection techniques in the form of interviews and documentation. The data analysis technique used is an interactive model consisting of data reduction, data analysis or display and drawing conclusions. The results of this study are that there are actors who collaborate in a triple helix in the management of CSR for BUMD West Java Province, which have different roles in achieving the same goal of implementing CSR to the community in a sustainable manner and supporting collaboration between the government and the community and companies. This triple helix collaborative research is seen from the 3 actors who have the most significant influence on the CSR management process. The actors in question are from the West Java Provincial Government through the CSR Facilitation Team (Government), BUMD Actors, namely PT. Migas Hulu West Java (entrepreneurs), and the role of academics as well as groups receiving CSR programs. The recommendation in this study is that the West Java Government as the highest policy holder discusses CSR management as a prioritized policy agenda to help the West Java Government itself in the context of socializing and outreach of government cooperation with academic and community groups as well as supporting the West Java Provincial government in managing sustainable CSR. and have a major impact on society.